Factors affecting digital entrepreneurial intention among females - Pan, Hui Xin (2023)
In this digital era, the perspective of digital entrepreneurship is seen as an essential foundation for growth in the economy, jobs creation, and innovation. The Malaysian government has launched the National Entrepreneurship Policy 2030 to foster a heritage that supports entrepreneurship to keep ahead of the next industrial revolution. There are some issues with the aim of catching up with Substantial Development Goals (SDGs). Thus, this study will provide some effort or indicator to assist the relevant authorities in exploring their insight in terms of economic participation and opportunities among females that reduce poverty and gender inequality. The research objective is to examine the factors affecting digital entrepreneurial intention among females in the digital economy by using an integrated TAM and TPB model. Quantitative research via questionnaires is used for research design to conduct an empirical result. A deeper data analysis of the 376-sample size has been made. It shows that perceived ease of use and perceived usefulness of the digital platform will affect the attitude, whereas attitude and perceived behavioral control will influence the digital entrepreneurial intention among females. However, only subjective norm shows there is no significant relationship with digital entrepreneurial intention. This final year project has provided empirical results and findings for the digital entrepreneurial and female entrepreneurial.